Study of ZrO2 Content on Hardness and Wear Characteristic of Coatings. Issue 1 (1st January 2023) - Feng, Pei; Shi, Yuhua; Shang, Peng; Peng, Tongtong; Feng, Rongrong; Li, Bin; Zhao, Xinsheng
Abstract: Aluminum alloy has limited its application due to low hardness and poor wear resistance. Therefore, surface modification by electroplating is beneficial to improving hardness and wear resistance properties. Hence, Ni/W–ZrO2 coating was organized on aluminum alloy by electro-deposition method in this paper. The optimum organization parameters were obtained. The impact of different ZrO2 additions on the hardness and friction wear properties of Ni/W–ZrO2 coatings were further investigated. The SEM, Vickers examiner and wear examination are used to analyze the micromorphology, micro-hardness as well as friction and wear resistance properties, respectively. The results show that when the addition of ZrO2 was 40g/L in the deposition bath, the Ni/W–ZrO2 coating possesses the optimum micro-hardness of 384HV. This is mainly attribute to the dispersion-enhancing effect of ceramic particles. This work offers a new approach to surface strengthening technology for aluminum alloys.